A Cognitive Approach To Metaphor Translation : A critical analysis of “the city is a woman” metaphor translation in Yasmina khadra’s trilogy on the misunderstanding between Orient and Occident - Sahli, Khadidja Hana (Journal of Human Sciences, 2022)
Metaphor translation has attracted a lot of attention from scholars in translation studies, both in theory and practice, because rendering the metaphor’s meaning, when translating, poses a real challenge for the literary translator.This study aims to answer two major questions:1- What makes the metaphor translation a problematic issue?2- What are the best strategies that help the translator to overcome the difficulties involving the translation of metaphorical expressions?After an overview of how metaphor has been dealt in different previous works, this paper discusses a new model towards metaphors translation by analyzing the occurrences of the metaphor "The City Is A Woman" in three novels of Yasmina KHADRA – his trilogy on the misunderstanding between East and West- and their translations into Arabic. The analysis relies on Lakoff and Johnson’s cognitive theory as well as Mandelblit’s cognitive translation hypothesis.